2021
DOI: 10.1186/s12889-021-11030-1
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported sexually transmitted infections among sexually active men in Ghana

Abstract: Background In sub-Saharan Africa, sexually transmitted infections (STIs) other than HIV are major public health problems. This study, therefore, sought to assess the prevalence and factors associated with self-reported STIsamong sexually active men in Ghana. Methods Data from the 2014 Ghana demographic and health survey wereused to conduct the study. This research included a total of 3051 sexually active men aged 15–59 years. Self-reported STI was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
1
8
1
Order By: Relevance
“…This finding is consistent with previous studies which indicated that those whose age at first sex is below 20 years had higher odds of contracting or reporting STIs. 23 31–34 This finding reiterates the fact that early sexual debut is a risky sexual behaviour which may increase the odds of STI among AGYW. 35–37 Our finding implies that delaying sexual debut among young individuals carries a benefit in reducing the prevalence of STIs among AGYW.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…This finding is consistent with previous studies which indicated that those whose age at first sex is below 20 years had higher odds of contracting or reporting STIs. 23 31–34 This finding reiterates the fact that early sexual debut is a risky sexual behaviour which may increase the odds of STI among AGYW. 35–37 Our finding implies that delaying sexual debut among young individuals carries a benefit in reducing the prevalence of STIs among AGYW.…”
Section: Discussionmentioning
confidence: 68%
“… 40–42 Access to mass media may serve as a source of education on STIs and health-seeking which could positively influence individuals’ behaviour toward the identification of symptoms as well as testing for STIs. 23 42 43 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Media access (exposure) was the other factor found to be associated with STI. This factor was also found to be a factor for STIs in research studies in Ethiopia [ 14 ], Ghana [ 44 ], and sub-Sahara Africa [ 45 ]. This might be due to the differences in the respondent’s media access and media program choices.…”
Section: Discussionmentioning
confidence: 92%
“…prevalence in Kenya 19,20 The prevalence reported in this study is, however, lower than the findings reported from Ghana. 21 achieve viral suppression for at least 95% of those treated. 22 PNG should also strive towards this goal.…”
Section: Discussionmentioning
confidence: 99%